Biochar Implications Under Limited Irrigation for Sweet Corn Production in a Semi-Arid Environment - Singh, Manpreet; Singh, Sukhbir; Parkash, Ved; Ritchie, Glen; Wallace, Russell W.; Deb, Sanjit K. (Frontiers in Plant Science, 2022)
Integration of biochar and deficit irrigation is increasingly being evaluated as a water-saving strategy to minimize crop yield losses under reduced irrigation in arid and semi-arid regions such as West Texas. A two-year (2019 and 2020) open-field study evaluated the effect of two types of biochar amendments (hardwood and softwood) and three irrigation rates [100%, 70%, 40% crop evapotranspiration (ETc) replacement] on physiology, plant growth, and yield of sweet corn in semi-arid West Texas. All experimental units were replicated 4 times in a split-plot design. The chlorophyll content (ChlSPAD) in 40% ETc dropped significantly compared to 100% ETc and 70% ETc during the reproductive phase. Although water stress under 40% ETc decreased photosynthesis (Pn) to limit transpiration (E) by stomatal closure, it improved intrinsic water use efficiency (iWUE). The above-mentioned gas exchange parameters were comparable between 100% ETc and 70% ETc. Both biochar treatments increased ChlSPAD content over non-amended plots, however, their effect on gas exchange parameters was non-significant. All growth and yield-related parameters were comparable between 100% ETc and 70% ETc, but significantly greater than 40% ETc, except water productivity (WP). Both deficit irrigation treatments improved WP over full irrigation in 2019, but in 2020 WP gains were observed only under 70% ETc. Hardwood biochar decreased soil bulk density and increased soil porosity, but it had a marginal effect on water retention characteristics. These results suggest that 70% ETc can be used as an alternative to full irrigation to save water with a minimal yield penalty for sweet corn production in the West Texas region. Hardwood biochar application improved the vegetative biomass significantly but yield marginally during the first two years of application. A long-term study is required to test the effect of biochar under deficit irrigation beyond two years.